Sex differences in Y-balance performance in elite figure skaters - Slater, L. V.; Vriner, M.; Schuyten, K.; Zapalo, P.; Hart, J. M. (The Journal of Strength and Conditioning Research, 2020)
Asymmetrical dynamic balance compared with normative populations have been associated with increased risk of injury in athletes; however, it is unclear if the current data are similar to balance performance in figure skaters. Therefore, the purpose of this study was to compare performance on the Y-balance test between sexes and disciplines in elite figure skaters. Thirty-two senior level figure skaters from 3 different disciplines (singles, dance, and pairs) completed the Y-balance test on the take-off and landing leg. Absolute differences between limbs (cm), normalized differences between limbs (% leg length), and composite scores (CSs; % leg length) were calculated for all skaters. A multivariate analysis of variance was used to identify differences in performance based on discipline and sex. Females had a greater absolute difference between limbs (mean difference = -3.62 cm) and a greater normalized difference between limbs on the posterolateral (PL) reach compared with males (mean difference = -4.26% leg length). Ice dancers had larger CSs on the take-off leg compared with pair skaters (mean difference = 6.42%). These results suggest that male and female figure skaters demonstrate differences in dynamic balance in the PL direction, with female skaters exhibiting decreased reach on the landing leg, which may suggest asymmetrical hip strength in female figure skaters and increase risk of lower extremity injury in the landing leg. Sport performance professionals should consider these sex differences when designing strength programs for elite figure skaters.